2015
DOI: 10.1111/josh.12340
|View full text |Cite
|
Sign up to set email alerts
|

Multilevel Factor Structure and Concurrent Validity of the Teacher Version of the Authoritative School Climate Survey

Abstract: The teacher version of the ASCS can be used to assess 2 key domains of school climate and associated measures of student engagement and aggression toward peers and teachers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
32
1
5

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 36 publications
(39 citation statements)
references
References 32 publications
1
32
1
5
Order By: Relevance
“…Finally, we concluded with estimates of internal consistency reliability by use of omega composite reliability, assess levels of measurement error at different levels in the analysis. Several researchers have posited the necessity of examining whether test's qualities are stable across different levels of analyses [16,22,23], since ignoring nesting may lead to inconsistencies and inaccuracies of the obtained estimates (e.g., due to violation of the independence of observations assumption) as well as theoretical misjudgments (e.g., concluding on a global simple structure when different ones are present at each level in the analyses). First, we run a CFA on the nine (9) subscales of the PrfEng scale, in order to establish a strong measurement model for the test under consideration.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, we concluded with estimates of internal consistency reliability by use of omega composite reliability, assess levels of measurement error at different levels in the analysis. Several researchers have posited the necessity of examining whether test's qualities are stable across different levels of analyses [16,22,23], since ignoring nesting may lead to inconsistencies and inaccuracies of the obtained estimates (e.g., due to violation of the independence of observations assumption) as well as theoretical misjudgments (e.g., concluding on a global simple structure when different ones are present at each level in the analyses). First, we run a CFA on the nine (9) subscales of the PrfEng scale, in order to establish a strong measurement model for the test under consideration.…”
Section: Discussionmentioning
confidence: 99%
“…First, the developer tests whether a pre-defined set of relationships among latent variables and specific items is stable across levels [22]. Second, the developer investigates internal characteristics of the measure, and may identify factors that affect the content of the items making them to operate differently at the different levels of the analysis (e.g., scale items are homogeneous only at the between level while there is large heterogeneity at the within level).Third, the developer may identify exogeneous factors (e.g., gender, race, etc.)…”
Section: Introductionmentioning
confidence: 99%
“…Preliminary factor analyses indicated a similar pattern of fit for the five-item PTB scale using teacher data (Huang, Cornell, Konold, Meyer, Lacey, Nekvasil, Heilbrun, & Shukla, 2014).…”
Section: Methodsmentioning
confidence: 82%
“…School climate has been defined broadly and inclusively, with a number of constructs and no unifying conceptual model that encompasses all of them. This study addressed two particular dimensions of school climate that previous studies (Huang et al, 2015;Konold et al, 2014;) have found to be especially important.…”
Section: Limitations and Direction For Further Studymentioning
confidence: 99%
“…Authoritative schools, which are characterized as both demanding and responsive, have more positive academic outcomes (Lee & Cornell, 2012; and greater levels of academic engagement (Pellerin, 2005), meaning that students are less likely to be absent or unprepared for class compared with schools with a more permissive or indifferent climate. Further, authoritative schools have a lower school-wide prevalence of teasing and bullying Cornell, Shukla, & Konold, 2015;Konold et al, 2014), and students engage in less physical and verbal aggression with peers and teachers (Berg & Cornell, under review;Gregory, Cornell, & Fan, 2012) There has been relatively little research about the link between authoritative school climate and suspension rates. measured this relationship by using student and teacher school climate survey data to assess authoritative school climate and school records of school suspension rates.…”
Section: Authoritative School Climatementioning
confidence: 99%